Comfort and conformity: A culture-based theory of migration - Ruxanda Berlinschi; Jan Fidrmuc (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2018)
This paper proposes a theory of migration decisions in which cultural traits play a role. Individuals are assumed to value comfort (high wages) and conformity (interactions with individuals who share similar world views). Regions are assumed to differ economically (average wages) and culturally (average world views and their diversity). The model shows that self-selection of inter-regional migrants on world views is non-monotonic if one region is more diverse than the other, and it weakens with economic gaps between regions. This non-monoticity can lead to a dichotomy of outcomes: culturally diverse regions become even more diverse because of migration, while culturally homogeneous regions become even more homogeneous. Consequently, Tieboutian sorting (people moving to the region in which world views are closer to theirs) only holds when regions have similar wages and diversity of world views.
Keywords: A13; F22; J61; Z1; 330; Migration; self-selection; culture; diversity